Effects of Fermented Red Rice Bran on Gut Microbiota Modulation and Colorectal Cancer Prevention in a DMBA-Induced Mouse Model - Anasyua, Fairuz Khairunnisa; Cahya, Sella Nur; Hanifah, Azka Khansa; Kusuma, Rio Jati; Rahmawati, Dini; Widyaningsih, Wahyu (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2025)
Colorectal cancer prevention is closely linked to gut microbiota modulation, particularly by increasing lactic acid bacteria (LAB) and short-chain fatty acids (SCFA). This study investigates the effect of fermented red rice bran on colon microbiota improvement. Fermented bran was produced by mixing red rice bran with water and yeast, followed by an analysis of the proximate composition, dietary fiber, resistant starch, antioxidants, and phenols. A quasi-experimental study was conducted on 30 mice, assigned to normal, negative control, 10% bran, 20% bran, 10% fermented bran, and 20% fermented bran groups. Colorectal cancer was induced using DMBA (20 mg/kgBW) intraperitoneally four times over two weeks. Treatment groups received bran or fermented bran ad libitum for 14 days. Cecal analysis showed that 20% red rice bran and 10% fermented bran significantly increased SCFA levels (p < 0.05), suggesting improved microbiota function, but did not significantly alter pH or LAB counts. These findings highlight the potential of fermented red rice bran in modulating gut microbiota, though further studies are needed to elucidate its long-term effects and mechanisms in colorectal cancer prevention.